TAKTIK RETORIS NAJWA SHIHAB PADA PROGRAM TALK SHOW MATA NAJWA DI METRO TV - Rofii, Afif; Yuniarti, Lisa (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
The research aims to describe the rhetorical tactics used by Najwa Shihab on the Mata Najwa talk show program that aired on one of Indonesia’s private television stations, Metro TV. This type of research is qualitative research analyzed by descriptive method. The data type is qualitative data which is the result of conversation transcript of the Mata Najwa talk show Sang Penantang  episode which aired on Metro TV. As for data collection technique used is a listening technique with data collection instruments in the form of field records. Based on the findings and analysis, it can be drawn to the conclusion that the rhetorical tactics used by Najwa Shihab in the Mata Najwa on Sang Penantang episode are affirmation and offensive tactics. The affirmation tactive is used by Najwa Shihab to ask questions that are explaining something or asking for approval from the source. "The affirmation tactics used by Najwa Shihab in this program include ""yes"", repeat tactics, togetherness tactics and compromise tactics." Offensive tactics are used by Najwa Shihab to dig up information that is justification, defense and recognition. Offensive tactics used include anticipation tactics, surprising tactics, asking back tactics, provocation tactics, encompassing tactics and overestimating tactics